PERSEPSI MAHASISWA YANG MENDORONG PERILAKU MEROKOK DI LINGKUNGAN KAMPUS: PENDEKATAN KUALITATIF - Fakhreni Fakhreni; Putra Apriadi Siregar (Jurnal Kesehatan, 2023)
This study aims to determine Student Perceptions that Encourage Smoking Behavior in the Campus Environment: A Qualitative Approach. The research design to be used is descriptive qualitative with a case studies approach. The results of the study found that all informants started smoking when they were still in junior high school. In conclusion, students often feel bored with academic activities and are already very addicted to cigarettes. This makes it difficult for students to refrain from smoking in the campus environment. The campus also has no policy regarding smoking in the campus environment, and smoking in the campus environment is not done by students as well, but the staff and lecturers also often smoke in the campus environment.